The Most Favored Nation Clause: a Review - Torres Reyes, Brigitte (2019)
In this article, inter-State relations are approached from a juridical-economic perspective to identify the origin for excessive transaction costs in this area. The political and administrative decisions made at the international level and the problems that come with the actions adopted are analyzed without a rational examination of the regulations in question. This article focuses on the study of the most favored nation clause, a figure of International Commercial Law enshrined in the General Agreement on Tariffs and Trade. JEL CODE / CLASIFICACIÓN JEL: F02, B31